2017
DOI: 10.1073/pnas.1621072114
|View full text |Cite
|
Sign up to set email alerts
|

Song hybridization events during revolutionary song change provide insights into cultural transmission in humpback whales

Abstract: Cultural processes occur in a wide variety of animal taxa, from insects to cetaceans. The songs of humpback whales are one of the most striking examples of the transmission of a cultural trait and social learning in any nonhuman animal. To understand how songs are learned, we investigate rare cases of song hybridization, where parts of an existing song are spliced with a new one, likely before an individual totally adopts the new song. Song unit sequences were extracted from over 9,300 phrases recorded during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 55 publications
5
94
0
Order By: Relevance
“…Hundreds of laboratory experimental studies have demonstrated social learning and transmission in a wide variety of animals. Social learning is now extensively documented in mammals (29), with a particular intensity of research studies in primates (30)(31)(32)(33) and cetaceans (34)(35)(36)(37), in birds (38)(39)(40)(41), in fish (42), and in insects (43,44). The fact that social learning has been shown to play important roles spanning multiple functional contexts (25)(26)(27)(28) suggests that many animals are not simply acquiring one or a few behavioral patterns socially, but rather that social learning is central to their acquisition of adaptive behavior.…”
Section: The Discovery Of Widespread Animal Culturementioning
confidence: 99%
See 3 more Smart Citations
“…Hundreds of laboratory experimental studies have demonstrated social learning and transmission in a wide variety of animals. Social learning is now extensively documented in mammals (29), with a particular intensity of research studies in primates (30)(31)(32)(33) and cetaceans (34)(35)(36)(37), in birds (38)(39)(40)(41), in fish (42), and in insects (43,44). The fact that social learning has been shown to play important roles spanning multiple functional contexts (25)(26)(27)(28) suggests that many animals are not simply acquiring one or a few behavioral patterns socially, but rather that social learning is central to their acquisition of adaptive behavior.…”
Section: The Discovery Of Widespread Animal Culturementioning
confidence: 99%
“…For example, archaeological excavations have shown remains of nut-cracking materials dated to 4,300 y below the surface of the Taï Forest, where modern chimpanzees continue this practice, absent in most parts of Africa (31,46); 27 y of observations have documented the spread from a few to over 600 humpback whales of a new form of hunting technique, lob-tail fishing (47); and new humpback songs have been found to emerge, spread quickly to whole populations, and pass in waves across the Pacific in consecutive years (36,37).…”
Section: The Discovery Of Widespread Animal Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Acoustic communication is one of the few natural behaviours that can be easily recorded, digitized and studied (Catchpole & Slater, ; Cocroft & Rodríguez, ; Garland, Rendell, Lamoni, Poole, & Noad, ; Ryan & Guerra, ). Often, behavioural studies involve laboratory observations, which can lead to fundamental insights but may disrupt natural animal behaviour (Fehér, Wang, Saar, Mitra, & Tchernichovski, ; Marler & Peters, ; Searcy, ).…”
Section: Introductionmentioning
confidence: 99%